Distribution of Fe, Pb, Cu, Cr and Cd in the Flesh, Gills and Liver of Fish (Synodontis Batensonda) Samples from River Galma, Zaria, Nigeria - Mohammed, Y; Bala, A. R (International Journal of Chemistry and Materials Research, 2015)
Iron, lead, copper, chromium and cadmium concentrations were determined in the flesh, gills and liver of fish (Synodontis batesonda) samples collected at ten different points along River Galma in Zaria, Kaduna State using atomic absorption spectrophotometer (AAS). Except for the concentration of iron (Fe) in the liver, the concentrations of all the metals analysed in the three organs depict the pattern: gills > liver > flesh. The concentrations of these heavy metals in fish gills and liver is much higher than that in flesh. The profile mean metals concentration in the flesh is Fe > Pb> Cu > Cr > Cd, while in the gills and liver is Fe > Pb > Cr > Cu > Cd. Iron and lead are the most abundant elements in the fish samples studied. The concentrations of the metals in this study were lower than the maximum permissible limits of NESREA and WHO. Stringent measures need to be enforced by the authority on illicit discharge of industrial and domestic wastes into the river.